1998
DOI: 10.1515/hfsg.1998.52.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Lignin Content ofEucalyptus globulusWood Using FTIR Spectroscopy

Abstract: FTIR spectroscopy was used to quantitatively determine lignin in Eucalyptus globulus wood. A total of 40 wood samples from a 9 year old provenance trial was divided into two independent sets for calibration and validation. Lignin contents, as determined by the acetyl bromide method, ranged from 23 % to 34 % o.d. extractive-free wood. Spectra were recorded with the KBr pellet technique and twelve peaks between 1800cm" 1 to 800cm" 1 used for calibration by linear regression. The best calibration fit (R 2 = 0.98)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 215 publications
(95 citation statements)
references
References 7 publications
7
88
0
Order By: Relevance
“…The absorption peak position and relative intensity of the FTIR results reflected changes in the cellulose, hemicellulose, and lignin components in different functional groups (Francioso et al 2011). Rodrigues et al (1998) used FTIR spectroscopy to quantitatively determine the amount of lignin in Eucalyptus globulus, and they concluded that the best calibration fit was obtained using peak height ratios at 1505 and 1158 cm -1 for lignin and carbohydrates, respectively. In this study, the intensities at 1505 and 1158 cm -1 decreased and were almost absent after returning for 3 years, which likely indicates that part of the lignin and carbohydrates were removed.…”
Section: Discussionmentioning
confidence: 99%
“…The absorption peak position and relative intensity of the FTIR results reflected changes in the cellulose, hemicellulose, and lignin components in different functional groups (Francioso et al 2011). Rodrigues et al (1998) used FTIR spectroscopy to quantitatively determine the amount of lignin in Eucalyptus globulus, and they concluded that the best calibration fit was obtained using peak height ratios at 1505 and 1158 cm -1 for lignin and carbohydrates, respectively. In this study, the intensities at 1505 and 1158 cm -1 decreased and were almost absent after returning for 3 years, which likely indicates that part of the lignin and carbohydrates were removed.…”
Section: Discussionmentioning
confidence: 99%
“…Watkins et al [66] used FTIR-ATR to characterize organosolv lignins. FTIR spectral data were also used to model lignin content in wood of, e.g., Picea sitchensis [67], Picea abies [68] and Eucalyptus globulus [69].…”
Section: Fourier Transform Infrared (Ftir)mentioning
confidence: 99%
“…The lignin content determined by wet chemical analysis ranges from 15 to 28% [105][106][107]. Using the acetyl bromide method, Rodrigues et al [69] obtained a lignin content of 23-34% (in extractive-free base), and a similar range by FTIR modeling. The monomeric composition analysis shows that it is a GS-lignin with minor amounts of H units.…”
Section: Eucalyptusmentioning
confidence: 99%
“…Bands at 1330, 1220 and 1120 cm -1 are corresponding to syringyl unit, whereas small bands at 1275, 1153 and 1037 cm -1 are assigned to guaiaxyl unit of lignin molecules 12 . In general, the IR spectra of soda lignin isolated from different concentration levels were found to be the same suggesting that the general composition of lignin is not affected by the concentration and types of acids used.…”
Section: Resultsmentioning
confidence: 99%